Dirty Containers. - Heinbach, Christoph (Diplomica Verlag, 2012)
Hauptbeschreibung Globalization is regarded as the key driver of growing container trade activities due to economic development. With a technology relying heavily on the combustion of fuel, international shipping is responsible for 2.7 percent of total world emissions and ocean transportation is becoming increasingly linked to environmental problems. The concepts of sustainability and greener shipping are expected to be the prime focus of transportation in the coming decades, but the impending developments require a deep understanding of the emission impact and costs related to the inputs and.